Evaluation of the triple aim of medicine in prehospital telemedicine: A systematic literature review. (December 2020) - Culmer, Nathan; Smith, Todd; Stager, Catanya; Meyer, Hannah; Quick, Sarah; Grimm, Katherine
Objectives: With telemedicine becoming more widely implemented in emergency situations, understanding the quality and content of current findings that explore prehospital telemedicine is vital to establish best practices and guide future research. This systematic review examines the clinical importance of telemedicine in patient-provider ambulance-based settings with a focus on multifunctional systems for general prehospital emergency populations. Methods: Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses methodology we found 1564 abstracts, which were blind-reviewed by independent reviewers. Relevant articles were reviewed, classified, and analyzed according to research methods and technology type, as well as quality, cost, and satisfaction. The studies were also reviewed for validated evidence-based practice. Results: Those studies that looked at cost, quality, and satisfaction with care generally shared favorable results. Setup notwithstanding, cost was comparable or less than controls. Care quality was also found to be in line with or slightly preferable to face-to-face care with some advantages in response time and quality. Patients and providers were satisfied with the systems. Common obstacles included limited bandwidth and small sample sizes. Conclusions: Although feasibility remains salient, research regarding the impact of ambulance-based telemedicine on patients and healthcare providers is encouraging, but nascent. As a whole, this body of literature does not yet adequately speak to the most important concerns of medicine: quality, cost, and satisfaction. More research is needed in each of these areas. However, those studies that do address these matters share hopeful results. Future research should test these mechanisms in prehospital settings with greater rigor.